A simple and effective strategy for detecting artemisinin based on oxidative cyclization of vitamin B1 eliciting fluorescence turn-on. Issue 1 (6th December 2018) - Zou, Wu; Gong, Fuchun; Cao, Zhong; Xia, Jiaoyun; Gu, Tingting; Deng, Renxing
Abstract : Artemisinin (ART) and its derivatives are first-line treatment drugs for falciparum malaria and save millions of lives every year. A VB1 -based fluorogenic probe for ART determination was developed by measuring the products of VB1 oxidized by ART. Abstract : Artemisinin (ART) and its derivatives are first-line treatment drugs for falciparum malaria and save millions of lives every year. It is very difficult to design specific fluorescent probes for ART because ART has no groups for binding to except for the peroxide group. We find that alkaline-hydrolyzed ART (a-ART) can specifically recognize and react with vitamin B1 (VB1 ) and produce fluorimetrically detectable thiochromes. Notably, this chemistry is affected by very low concentrations of a-ART in a Tris–HCl buffer solution (pH 7.5) at room temperature, leading to >260-fold enhancement in the blue emission at 442 nm. By making use of the new signaling mechanism, an effective strategy for detecting ART was developed. The fluorescence intensity of the VB1 -based probes linearly increased with increasing ART concentration ranging from 1 to 230 μM mL −1, and a detection limit as low as 11.5 nM mL −1 was achieved, making this method more sensitive than other reported UV-vis absorption and electrochemical methods. Moreover, this assay shows good selectivity over other ions and biomolecules. The proposed method was applied for the determination of ART in tablets and dried leaf samples of Artemisia annua L. with satisfactory results, which confirms its great potential for real sample analysis. The designed assay avoids the preparation of fluorescent probes, and all the detection processes are accomplished within 20 min. Therefore, VB1 can offer a simple, highly sensitive and selective sensing model for fluorescence detection of ART.